Performance of Relay Assisted STBC Coded MIMO Wireless Downlink Communication - M.M. Kamruzzaman (Institute of Advanced Engineering and Science, 2014)
In this paper, performance of relay assisted wireless link is evaluated in the presence of rayleigh fading where source (base Station) is equipped with multiple single transmit antenna, relay is equipped with multiple transmit and receive antennas, and destination (mobile handset) has single receive antenna. Data are modulated using QPSK or 16 QAM or 64 QAM modulator at handset and send to relay which combined and decode the incoming signal using Maximum Likelihood decoding and further encode the symbols using STBC, and the encoded data are split into n streams which are simultaneously transmitted using n transmit antennas of relay. It is observed that relay assisted system having with different combination of transmit and receive antennas at relay provides 11-13 dB gains compared to direct link at 10-5.